A study comparing vaginal misoprostol alone with vaginal misoprostol in combination with Foley catheter for cervical ripening and labour induction - Bhatiyani, Binti R.; Gandhewar, Manisha R.; Kapsikar, Swati; Gaikwad, Pradip (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labor is a commonly practised intervention in modern obstetrics. The objective of this study was to compare the efficacy of vaginal misoprostol alone with vaginal misoprostol in combination with Foley catheter for labour induction. It aims to assess the induction delivery interval, the outcome of labour, the incidence of instrumental delivery and Cesarean section. The neonatal outcomes and maternal complications would also be assessed. Methods: 105 women with singleton viable pregnancies of 28 weeks or more gestation with cephalic presentation, intact membranes and an unfavorable cervix (Bishops score less than 6) were randomly assigned to induction of labor using vaginal misoprostol or Foley catheter in combination with vaginal misoprostol. Women in the misoprostol only group received 25 micrograms of misoprostol per vagina every 4 hours for a maximum of six doses. Whereas women in the combination group received vaginal misoprostol and in addition Foley catheter was introduced through the cervix for 12 hours. Interruption of the trial was done in case of failure to enter the active phase of labour after 24 hours of induction, fetal distress, hyperstimulation, hypersensitivity to drugs. Results: The induction to delivery time was shorter in misoprostol group as compared to the Foley with misoprostol group by 3 hours. There was no significant change in Bishops score after induction with Foley in combination with misoprostol as compared to misoprostol alone. There was no increase in the maternal and fetal complications in the misoprostol group as compared to Foley with misoprostol. Conclusions: Misoprostol alone was more efficacious for ripening and inducing agent as compared to Foley in combination with misoprostol.